Tropical frogs as a model system to understand host-pathogen-microbiota interactions (2016)
In my thesis, I undertook a broad survey of Bd in wild amphibian populations using non-invasive molecular techniques, and using natural history traits of the host along with spatial climatic parameters. I found that Bd is geographically and taxonomically widely distributed, and its presence is best explained by environmental parameters related to temperature and precipitation. Since Bd was also detected in Lowland species of the threatened genus Atelopus, I examined whether the species tested positive for Bd harbor cutaneous symbiotic bacteria capable of inhibiting Bd growth, allowing them to survive. Atelopus aff. elegans was the only species that tested positive for Bd, and holds the skin bacteria with the strongest anti-Bd action. This suggests that bacterial communities may have resulted from natural selection represented by Bd infection. In order to evaluate whether Bd can be considered as a potential tln. eat for Atelopus species, I also assessed Bd prevalence and infection intensity by examining live animals during contemporary field surveys and archived museum specimens. My results showed a decrease in abundance of A. spurrelli suggesting that Bd may have contributed to the apparent decline. In contrast, A. aff elegans remain stable despite the presence of the pathogen fltting an enzootic pattem ofhost/pathogen dynamic. I also evaluated the impact of captivity on the beneficial skin-associated bacterial community. Currently, the only method that has been proposed as an effective way to avoid the extinction of amphibian species is the establishment of captive assurance colonies. Therefore it is imperative to understand and evaluate how captivity could affect the disease dynamics and outcomes. Interestingly, I found that frogs in captivity still harbor bacteria with anti-Bd activity suggesting that captivity programs do not necessarily change bacterial communities of the toad skin in a way that impedes Bd growth control. Lastly, using as a study model two sympatric species of Andean frogs, Dendropsophus labialis and Rheobates palmatus, I provided key information on how microbial pathogen interactions differ across life stages, and how changes in bacterial community composition may affect the response to Bd infection. This thesis highlights the importance of using holistic approaches to better understand disease outcomes in diverse frog species and environments, and informs of possible mitigation efforts that can be implemented in the near future to help control and reduce Bd outbreaks